Impact of a mentored student clerkship on underrepresented minority diversity in otolaryngology–head and neck surgery. (14th April 2016) - Nellis, Jason C.; Eisele, David W.; Francis, Howard W.; Hillel, Alexander T.; Lin, Sandra Y.
Abstract : Objectives/Hypothesis: To describe the impact of a mentored clerkship initiative on underrepresented minority medical students interested in otolaryngology–head and neck surgery (OHNS). Study Design: Prospective observational study. Methods: An outreach effort to recruit underrepresented minority students was initiated in 2008, consisting of either a 3‐month research clerkship or a 1‐month clinical rotation. Financial assistance and faculty mentorship was provided for students. Upon conclusion of the clerkship, students completed a post‐clerkship evaluation form. Students were followed regarding residency applications, match status, and publications. Evaluations were compiled and analyzed. The number of publications resulting from interaction with faculty mentors was calculated. Results: Fifteen students participated in the clerkship from 11 medical schools. Of those, 10 students participated in the clinical clerkship, four in the research clerkship, and one in both clerkships. Evaluation (5‐point Likert scale) average scores and comments revealed high student satisfaction with the rotations (4.85), provided individual mentorship (4.85), and provided exposure to academic medicine (4.92). Participants indicated the rotation favorably impacted their decision to apply for OHNS residency training and increased their interest in academic medicine. The participants had an average number of 1.7 publications, with 1.18 publications in OHNS journals. Six publications resulted from direct interaction between students and faculty during the clerkship. Seven students applied for OHNS residency programs, and six matched successfully. Conclusion: Mentored clerkships for underrepresented minority medical students increases interest in applying to OHNS residency training programs and is a successful approach to increasing physician diversity. It provides a pathway to expand research opportunities and increase student interest in academic medicine. Level of Evidence: NA Laryngoscope, 126:2684–2688, 2016